Pelatihan Daur Ulang Sampah Botol Plastik Sebagai Media Pembelajaran Pengelolaan Sampah Dan Kreativitas - Rina Sulistiyani (Jurnal Pengabdian Masyarakat - PIMAS, 2022)
The volume of waste that continues to increase, especially plastic waste requires appropriate management strategies, one of which is through recycling. Plastic bottle recycling training aims to increase knowledge of dealing with plastic waste and develop the creativity of elementary school students through training on recycling plastic bottle waste. Implementation methods include environmental observations, problem identification, determination of service activities, coordination of service activities with prospective participants, implementation of training. The waste recycling training activity has been successful and running smoothly, able to develop creativity and increase participants' knowledge regarding plastic waste management. Supporting factors for success include the motivation of participants to use the training as a source of new knowledge, increase skills, as a means to relieve boredom during the pandemic and thanks to the support of parents. Keywords : creativity, learning, recycling, training, waste ABSTRAK Volume sampah yang terus meningkat, utamanya sampah plastik menuntut strategi pengelolaan yang tepat, salah satunya melalui daur ulang. Pelatihan daur ulang sampah botol plastik bertujuan untuk meningkatkan pengetahuan mengatasi sampah plastik dan mengembangkan kreativitas siswa Sekolah Dasar melalui pelatihan daur ulang sampah botol plastik. Metode pelaksanaan mencakup pengamatan lingkungan, identifikasi masalah, penentuan kegiatan pengabdian, koordinasi kegiatan pengabdian dengan calon peserta, pelaksanaan pelatihan. Kegiatan pelatihan daur ulang sampah telah berhasil dan berjalan lancar, mampu mengembangkan kreativitas dan meningkatkan pengetahuan peserta terkait pengelolaan sampah plastik. Faktor pendukung keberhasilan antara lain motivasi peserta yang menjadikan pelatihan sebagai sumber pengetahuan baru, menambah ketrampilan, sebagai sarana untuk menghilangkan rasa jenuh selama pandemi dan berkat dukungan orang tua. Kata kunci : daur ulang, kreativitas, pelatihan, pembelajaran, sampah